Teen mothers who are daughters of teen mothers: Psychological intergenerational dimensions of early motherhood. (December 2017) - Margherita, Giorgia; Troisi, Gina; Tessitore, Francesca; Gargiulo, Anna
Abstract: Introduction: Researchers have shown that being a daughter of a teenage mother is a risk factor regarding the possibility of having early, unprotected sexual intercourse and of falling pregnant. The experiences of young mothers in such situations and the aspects of intergenerational transmission in the mother–daughter relationship have not been well investigated. Objectives: This study analyses the experience of motherhood in young mothers (18–20 years at the time of the interview/15–16 at the time of their pregnancy) who are daughters of teen mothers themselves from the psychodynamic perspective of intergenerational transmission. Methods: Six young mothers from Southern Italy were selected and interviewed. A semi-structured interview was used to explore the early experience of pregnancy and motherhood and their relationship with their own mothers. The interviews were analysed through Interpretative Phenomenological Analysis (IPA). Results: Five superordinate themes emerged: I didn't want, I didn't see and I didn't feel ; Adolescence? I suddenly became a mother ; History repeats itself again and again ; Confused Spaces and How difficult is coming into the world? Conclusion: Adolescent mothers, who themselves are daughters of teen mothers, seem to have difficulty in representing the meanings associated with their experience of pregnancy and motherhood. A lack of narrative transmission of the experience of pregnancy from mothers to daughters emerged. The implications for research and social policies will be discussed. Highlights: Unexpected pregnancies are more likely in daughters of teenage mothers. Experience of motherhood in young mothers, daughters of teen mothers, was explored. A lack of narrative transmission of the pregnancy, birth and nurturing emerged The study shows how unthinkable elements passed on from one generation to another. Further researches focused on the study of the trans-generational dimensions needed.